Combating 'maritime terrorism' off the coast of Somalia - Anja Shortland; Marc Vothknecht (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper evaluates the effectiveness of the international naval mission in the Gulf of Aden from 2008-2010, both in terms of its counter-piracy and its counter-terrorism objectives. We draw on arguments developed in the literature of law and economics, detailed statistical analyses and a large number of in depth interviews. Counter-piracy operations are a qualified success: their main effects are the stabilisation of attacks at a high level and the substitution between the relatively well protected transit corridor in the Gulf of Aden and the open sea. However, the counter-piracy measures appear to deter pirates from forming alliances with Islamist movements and may therefore make a major contribution to international security.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: K42; O17; F19; 330; Piracy; Somalia; counter-terrorism; law and economics; deterrence; naval intervention